Engineering education focusing on environmental management in Malaysia - Jami, Mohammed Saedi; Al-Mamun, Abdullah; Hussain, Jabir; Abdulazeez, Qabas Marwan (2015)
The purpose of this paper is to discuss the necessity and benefit of environmental engineering education for sustainable development and initiate some practical activities with regard to wastewater sludge management in Malaysia. As the amount of sludge produced is expected to increase, a large expenditure is required for handling, transport and disposal of the wastewater sludge. Untreated sludge is pathetic in causing environmental and public health hazard. Therefore, wastewater sludge requires optimum further treatment such as conditioning and stabilization to improve the dewaterability for economically efficient and safe disposal. The issue of environmental protection in general and sludge management in particular are not included in the school curriculum. Educating the young generation is necessary by integrating the environmental issues including sludge management into the courses at high school as well as college/university levels. We have to get the younger generation to understand the necessity of saving resources and not polluting the environment in order to achieve a sustainable development.